Kerja Sama Indonesia-Australia Dalam Mewujudkan Visi International Maritime Organization (IMO) Dalam Merealisasikan Laut Bersih - Ery Tri Januarsi; Agus Salim Burhanuddin (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
To realize one of the visions of the International Maritime Organization (IMO), Indonesia and Australia have collaborated in this research. The close relationship between the two countries in the field of maritime security has encouraged maritime cooperation initiatives from Indonesia to Australia, which is based on awareness of its potential importance for Indonesia-Australia maritime security. This research uses qualitative methods, which aim to in-depth understanding of the problems discussed. Data collection was carried out through a literature study that examined various data sources relevant to the problem. This research is descriptive in nature, prioritizing analysis and in-depth understanding of the problems discussed. Bilateral cooperation between the two countries is directed towards their respective national interests, especially in the context of the International Maritime Organization (IMO). Through the "Joint Declaration on Maritime Cooperation Plan of Action" between Indonesia and Australia, comprehensive cooperation was built to address various maritime issues in the Indo-Pacific region, including the maritime borders of Indonesia and Australia as well as marine environmental problems. One of the important points in the Joint Declaration on Maritime Cooperation Plan of Action meeting was the commitment of the Indonesian and Australian Governments to develop an action plan to support the realization of goals, especially the issue of environmental pollution.